Innovative technologies for information resources management - Khosrowpour, Mehdi, 1951- (Advances in information resources management,, 2008)
This book brings together compelling content related to the continually emerging technologies in areas of information systems such as Web services, electronic commerce, distance learning, healthcare, business process management, and software development. Focusing on the implications innovative technologies have on the managerial and organizational aspects of information resource management, this book provides academcians and practitioners with a requisite and enlightening reference source.